2004
DOI: 10.1081/ddc-120037483
|View full text |Cite
|
Sign up to set email alerts
|

Development and Evaluation of Glyburide Fast Dissolving Tablets Using Solid Dispersion Technique

Abstract: Glyburide is a poorly water-soluble oral hypoglycemic agent, with problems of variable bioavailability and bio-inequivalence related to its poor water-solubility. This work investigated the possibility of developing glyburide tablets, allowing fast, reproducible, and complete drug dissolution, by using drug solid dispersion in polyethylene glycol. Phase-solubility studies were performed to investigate the drug-carrier interactions in solution, whereas differential scanning calorimetry, X-ray powder diffraction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
50
0
1

Year Published

2006
2006
2025
2025

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(53 citation statements)
references
References 22 publications
2
50
0
1
Order By: Relevance
“…The DSC thermograms of gliclazide, PVP K30 and SD are shown in Figure 1. The sharp melting endotherm of pure gliclazide appeared at 168.9 o C, whereas small endotherm was observed in solid dispersions at 160.0 o C prepared with PVP K30, indicated the decreased intensity of crystalline nature [14]. It may be due to that the drug molecules were dispersed in the PVP.…”
Section: Solid State Characterizationmentioning
confidence: 92%
“…The DSC thermograms of gliclazide, PVP K30 and SD are shown in Figure 1. The sharp melting endotherm of pure gliclazide appeared at 168.9 o C, whereas small endotherm was observed in solid dispersions at 160.0 o C prepared with PVP K30, indicated the decreased intensity of crystalline nature [14]. It may be due to that the drug molecules were dispersed in the PVP.…”
Section: Solid State Characterizationmentioning
confidence: 92%
“…The powder is passed till it forms a heap and touches the tip of the funnel. The radius was measured and angle of repose was calculated by using the above formula 5,6 . From the results in Table 1, it is evident that the drug has very poor flow properties, as the compressibility index, Hausner's ratio and Angle of repose values are high.…”
Section: Methodsmentioning
confidence: 99%
“…Improvement in the solubility of glyburide by solid dispersion technique has been reported (18). Ammar et al (19) have shown that the association of water soluble polymers with glimepiridecyclodextrin systems leads to great enhancement in the dissolution rate of the drug.…”
Section: Introductionmentioning
confidence: 99%